Regeneration of Padauk (Pterocarpus dalbergioides) - Artificial and Natural - Balasubramanyam, M. S. (Indian Forester, 1937)
It discusses (1) whether the plantations have really cost so much per acre as to be "deemed a financial failure from the start" and (2) whether the results obtained in plantations are not as good as In natural regeneration.